A Simple Approach to Specifying Concurrent Systems - Lamport, Leslie (Proc. of ACM SIGCOMM. Communications of the ACM 32. Also appeared as SRC Research Report 15., 1989)
This is a "popular" account of the transition-axiom method that I introduced in [50]. To make the ideas more accessible, I wrote it in a question-answer style that I copied from the dialogues of Galileo. The writing in this paper may be the best I've ever done.